KOMPARASI NILAI EKONOMIS DAN EFISIENSI PADA SKEMA-SKEMA KERJA PLTS PADA PT. LENTERA BUMI NUSANTARA - Muhammad Azka Athallah; Unggul Wibawa; Teguh Utomo (Jurnal Mahasiswa TEUB, 2022)
Solar Energy System is a renewable energy that convert sun irradiation into electrical energy through photovoltaic cell. Solar Energy System is divided into 2 types, on-grid system and offgrid system. On-grid solar energy is a system which connected to the grid. Energy Management System (EMS) is implemented in the attempt to maximize the reduction of cost for electricity. EMS implemented is by transmitting electrical energy from battery at peak load time. Solar energy with this EMS (scheme 1) will be compared with solar energy when; all energy produced by solar cell is transmitted to user load (scheme 2), all energy produced by solar cell will be exported to the grid (scheme 3), and energy produced will goes to load, if there is excess energy, it will be imported to the grid (scheme 4). The efficiency difference caused by battery don’t drastically effect the economical factor because the efficiency difference is 0,63%. Scheme 1has the highest investment cost, net profit, and COE, but since its investment cost and maintenance cost is high, scheme 1 is not worth to implement. Based on NPV, scheme 1 is the only scheme that is worth to i